PENGARUH TAX AMNESTY DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BIREUEN TAHUN 2016 - Rizki Saputra; Safri Nurmantu (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
This research was conducted to analyze The Influence of Tax Amnesty, Tax sanctions toward compliance of taxpayers of KPP Pratama Bireuen. This Research is conducted in KPP Pratama Bireuen. This research using quantitative method. Analysis of data used through  instrument analysis research including validity test, reliability test, hypothesis test, correlation analysis, kolmogorof-smirnov test, multicollinearity test, heteroskedastisitas test, autocorrelation test, partial significant test, simultant significant test, simple linier regression analysis. The result showed partially Tax Amnesty has no significant effect on compliance of taxpayer, while Tax Sanctions have an positive significant effect  on compliance of taxpayer and simultaneously F Value Count = 51.345 greater than  F Table = 3.09 then H O rejected with significant level. This means  that the independent variable, Tax Amnesty and  Tax sanctions have a mutually significant influence on compliance of taxpayer. Thus increasing Tax Amnesty and Tax Sanctions also increasing compliance of taxpayer.